2018
DOI: 10.1016/j.jtcme.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Traditional plants used for the treatment of gynaecological disorders in Vedaranyam taluk, South India - An ethnomedicinal survey

Abstract: Gynaecological disorder is one of the most severe conditions under reproductive health. So we investigate and collect information from traditional practitioners on the use of medicinal plants for treatment of Gynaecological disorder in Vedaranyam taluk, Nagappattinam district of South India. The field study was carried out for a period of January 2014–January 2015 in Vedaranyam taluk, Nagappattinam district of South India. This is the first traditional medicine study in which statistical calculations about pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 28 publications
6
21
0
2
Order By: Relevance
“…It was found that older people (middle age, 53.55) with little formal or institutional education have a lot of knowledge about the uses of 12 medicinal plants despite that the younger with age between 15-29 years represented 51% of population. It is a profession dominate by the elderly and uneducated men like indicated by Balamurugan et al study [32] The average practice experience was 23 years. It was confirmed that traditional medicine was a current activity for TH/H in western of Burkina.…”
Section: Discussionmentioning
confidence: 94%
“…It was found that older people (middle age, 53.55) with little formal or institutional education have a lot of knowledge about the uses of 12 medicinal plants despite that the younger with age between 15-29 years represented 51% of population. It is a profession dominate by the elderly and uneducated men like indicated by Balamurugan et al study [32] The average practice experience was 23 years. It was confirmed that traditional medicine was a current activity for TH/H in western of Burkina.…”
Section: Discussionmentioning
confidence: 94%
“…Muchos estudios (3,29,30) han demostrado la gran diversidad de conocimientos sobre las plantas medicinales por parte de los practicantes de la medicina tradicional; sin embargo, la evaluación bioprospectiva de plantas medicinales y usos tradicionales también se puede determinar en los mercados locales y revelar sus riesgos y oportunidades, tanto para la salud como para el medio ambiente. La gran demanda de estos productos confirma su valor como recurso terapéutico y la importancia que tienen para las personas en el tratamiento de enfermedades; sin embargo, se requiere un mayor control sobre su venta para garantizar la salud pública y su disponibilidad a lo largo del tiempo.…”
Section: Discussionunclassified
“…Leaves of Sesbania grandiflora contain alkaloids, flavonoids, glycosides, tannin, anthraquinone, steroid, and terpenoid 38 . Traditionally the mixture of fresh leaves juices and coconut milk is used topically for skin diseases 39 . 100 g of fresh leaves contain 8 g protein, 1 g fat, 12 g carbohydrate, 2 g crude fiber, and 93 kcal energy.…”
Section: Vegetable Hummingbird (Sesbania Grandiflora)mentioning
confidence: 99%